IMPLEMENTASI TRAFFIC ACCIDENT ANALYSIS GUNA MENANGGULANGI KECELAKAAN LALU LINTAS - Fadlan; Kamaruddin; Arifai (Halu Oleo University, 2024)
This study aims to determine the Implementation of Traffic Accident Analysis to Overcome Traffic Accidents. This research method combines normative and empirical approaches to analyze the implementation of traffic accident analysis which aims to reduce traffic accidents. The data processing and analysis methods use data listing, data coding, tabulation, and data analysis. The results of the study indicate that the Implementation of Traffic Accident Analysis is an important strategic step to reduce the number of traffic accidents by utilizing accurate data and in-depth analysis. There are various internal and external factors that influence the effectiveness of this implementation at the Polres level, which are related to the quality and quantity of personnel, facilities and infrastructure, and public awareness. In order to reduce the number of accidents, fundamental improvements are needed in both internal and external factors. Improving the quality of education and training of police officers, implementing modern technology in Traffic Accident Analysis, and consistent law enforcement are important steps. In addition, education to the public and improving infrastructure facilities must be carried out simultaneously to achieve optimal results in traffic safety.